Cross-National Gender Gaps in Political Knowledge: How Much Is Due to Context?. (September 2016) - Fortin-Rittberger, Jessica
Although the majority of studies on political knowledge document lingering gender-based differences in advanced industrial democracies, most contributors have drawn such conclusions from a single or a handful of countries, using limited batteries of political information items. Exploiting a pooled data set of the Comparative Study of Electoral Systems encompassing 106 post-election surveys in forty-seven countries between 1996 and 2011, this article demonstrates that survey instrument–related factors, such as question format and content, as well as the overall difficulty of questions, are more consequential in shaping the size of gender gaps in political knowledge than institutional factors, such as electoral rules or opportunity structures. The research design of this article draws from almost three hundred different items measuring factual political knowledge using the broadest country coverage and most comprehensive approach to measurement to date.